2016
DOI: 10.1155/2016/8714587
|View full text |Cite
|
Sign up to set email alerts
|

Time to Endoscopy in Patients with Colorectal Cancer: Analysis of Wait-Times

Abstract: Objective. The Canadian Association of Gastroenterology Wait Time Consensus Group recommends that patients with symptoms associated with colorectal cancer (CRC) should have an endoscopic examination within 2 months. However, in a recent survey of Canadian gastroenterologists, wait-times for endoscopy were considerably longer than the current guidelines recommend. The purpose of this study was to evaluate wait-times for colonoscopy in patients who were subsequently found to have CRC through the Division of Gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 12 publications
0
22
0
3
Order By: Relevance
“…Since there is increasing use of direct-to-colonoscopy procedures to reduce wait times, [27,28] it is important to determine what type of information might make patients more comfortable with such a process. In our study, the predictors of willingness to go direct-to-colonoscopy for a future colonoscopy were the amount of different types of information received, being satisfied with the information received for the current colonoscopy and coming direct-to-colonoscopy for their current colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is increasing use of direct-to-colonoscopy procedures to reduce wait times, [27,28] it is important to determine what type of information might make patients more comfortable with such a process. In our study, the predictors of willingness to go direct-to-colonoscopy for a future colonoscopy were the amount of different types of information received, being satisfied with the information received for the current colonoscopy and coming direct-to-colonoscopy for their current colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, patient wait times from evaluation of symptoms concerning for gastrointestinal malignancy to diagnostic endoscopy are lengthening. In addition, the wait times are longer than the recommended maximum wait times set forth by the CAG and CCO [ 12 , 13 ]. In 2010, Sey et al reported that 46% of patients diagnosed with colorectal malignancy (N = 106) in London, Ontario, were subject to wait times longer than the recommended standard of care [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Sey et al reported that 46% of patients diagnosed with colorectal malignancy (N = 106) in London, Ontario, were subject to wait times longer than the recommended standard of care [ 14 ]. Similarly, in a 2015 Canadian hospital-based practice of ten gastroenterologists, Janssen et al reported that 58% of patients diagnosed with colorectal cancer (N = 246) experienced wait times longer than the recommended 60 days [ 13 ]. It has been suggested that the use of IHFs to provide patients with endoscopy is an option to decrease patient wait times by offsetting the workload of hospital-based endoscopic practices.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Other studies evaluating the waiting list time of CRC patients have also observed no difference in the proportion of more advanced cases when comparing delays of more and less than two months. 15 …”
Section: Recommendationsmentioning
confidence: 99%